Nephrotic-range proteinuria in a patient with dengue fever: a case report from Bangladesh - Ikhtaire, Shapur (IMC Journal of Medical Science, 2019)
We report a case of nephrotic range proteinuria with 24-hour urine protein level of 18.3 g/day, which developed following dengue fever (DF). The patient did not exhibit classical features of nephrotic syndrome (NS) and his renal function was not compromised during his illness. Proteinuria resolved without any specific treatment and precluded renal biopsy. Though the dengue fever and associated renal disorders are self-limiting, renal involvement in severe dengue infection is growingly seen in recent years and could cause increased mortality and long-term morbidity. IMC J Med Sci 2018; 12(2): 86-89